2020
DOI: 10.1021/acs.inorgchem.0c00472
|View full text |Cite
|
Sign up to set email alerts
|

Fast, Low-Cost Synthesis of ZnO:Eu Nanosponges and the Nature of Ln Doping in ZnO

Abstract: A low-cost template-free solution chemical route to highly porous nanocrystalline sponges of ZnO-EuO 1.5 with 0−5 mol % Eu is presented. The process uses Zn− and Eu−acetate− nitrate and triethanolamine as precursors in methanol. After evaporation of the solvent and heating at 200 °C for 3 min, crystalline ZnO:Eu sponges with minor amounts of organic residues were obtained. Heating to 400 °C replaced the organics with carbonate, which in its turn was decomposed at temperatures below 600 °C, forming ZnO:Eu spong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 137 publications
(305 reference statements)
3
34
0
Order By: Relevance
“…A short review focused on the synthesis and connected properties is given in the in ref. (48) besides general reviews on Ln-doped ZnO and their properties and more comprehensive reviews are found in (45,47).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A short review focused on the synthesis and connected properties is given in the in ref. (48) besides general reviews on Ln-doped ZnO and their properties and more comprehensive reviews are found in (45,47).…”
Section: Introductionmentioning
confidence: 99%
“…DFT modelling, using dimeric Eu 3+ ion pairs flanking a metal vacancy for charge neutrality placed in the ZnO structure, did not result in any significant reduction of the unit cellvolume, compared to a linear Vegard type model using the calculated ionic radius of 83.5 pm for four coordinated Eu 3+ ions. (48) This indicates that while it might seem possible for the flanking Eu 3+ ions to make use of the Zn 2+ -ion vacancy void between two Eu 3+ ions, the surrounding ZnO lattice would be compressed around the site, resulting in increased ZnO cell-parameters resulting in a small energy gain compared to larger clusters. Thus, while it was shown that the Eu 3+ ions resided within the ZnO crystals, without a clearly visible phase separation in TEM imaging or XRD analysis, their local dopant structure remained unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there has been an ongoing discussion on the reality and nature of such Eu-doped ZnO, not the least due the close to zero changes in XRD unit cell-dimensions observed with high levels of Eu 3+ doping. A short review focused on the synthesis and connected properties is given in the in ref.(48) besides general reviews on Ln-doped ZnO and their properties and more comprehensive reviews are found in (45,47).It has recently been proven beyond doubt, that the Eu 3+ ions are situated within the ZnO nanocrystals when using synthesis temperatures from 200 to 700 o C. (48,49) In these studies, TG analysis, XRD, XPS, IR spectroscopy, SEM, TEM-ED/EDS, STEM-EELS mapping, and optical measurements were used to describe the chemistry and structure of Eu doped ZnO. It was found that at 200 to 500 o C, there were also minor amounts of organic residues or carbonate present, besides the Eu 3+ ions.…”
mentioning
confidence: 99%
“…This allows to understand the unexpected doping structure and how the ZnO unit cell-dimensions can be retained on doping with high levels of large, alio-valent ions such as Eu 3+ .Furthermore, the changes in coordination over the temperature range, 200 to 900 o C, were examined to follow the Eu-dopant coordination; from the lowest synthesis temperature of 200 o C, to the clean, Eu-doped oxide obtained at 600 o C, and further into the temperature range, 700-900 o C, where the Eu is expelled from the ZnO to yield 5-10 nm sized c-Eu2O3 particles on the ZnO sponge surface.The Eu-doped ZnO microstructures were also further described with SEM and TEM imaging, although more thorough microscopy studies, including TEM-EELS mapping has been provided elsewhere. (48,49) The optical studies provided insight into the energy levels and properties of the minor defects in these materials, not accessible by the TEM and EXAFS probes.Based on the results obtained in this study, highly complex and to-date unforeseen molecularlike dopant structures are proposed that may shed light on various hard to explain magnetic and optical data for this kind of semi-conductor materials. The findings reported herein also point to a general possibility to form clusters of "misfit"-ions within rigid semi-conductor structures for the design of optical, magnetic, catalytic and transport properties, where typically a high dopant level is desired, while the semi-conductor properties are sensitive to disturbances in the semi-conductor lattice.…”
mentioning
confidence: 99%
See 1 more Smart Citation